Sunrise [videorecording (DVD)] - Blaney, Ronan; Pettyfer, Alex, 1990-; Yu, Crystal; Gao, William; Yaeger, Kurt, 1977-; Fouéré, Olwen; Pearce, Guy, 1967- (Lionsgate, 2026)
When an ex-cop named Fallon returns to the scene of a horrific crime, the residents of a rural town soon discover that this dark visitor is really a vampire who feeds on blood and fear. After he is befriended by a kind immigrant family, the instinctive killer is faced with a choice between revenge and redemption.